Primary motor hand area corticospinal excitability indicates overall functional recovery after spinal cord injury - Chun-Qiu Dai; Chun-Qiu Dai; Ming Gao; Xiao-Dong Lin; Bai-Jie Xue; Ying Liang; Mu-Lan Xu; Xiang-Bo Wu; Gui-Qing Cheng; Xu Hu; Chen-Guang Zhao; Hua Yuan; et al. (Frontiers in Neurology, 2023)
BackgroundAfter spinal cord injury (SCI), the excitability of the primary motor cortex (M1) lower extremity area decreases or disappears. A recent study reported that the M1 hand area of the SCI patient encodes the activity information of both the upper and lower extremities. However, the characteristics of the M1 hand area corticospinal excitability (CSE) changes after SCI and its correlation with extremities motor function are still unknown.MethodsA retrospective study was conducted on the data of 347 SCI patients and 80 healthy controls on motor evoked potentials (MEP, reflection of CSE), extremity motor function, and activities of daily living (ADL) ability. Correlation analysis and multiple linear regression analysis were conducted to analyze the relationship between the degree of MEP hemispheric conversion and extremity motor function/ADL ability.ResultsThe CSE of the dominant hemisphere M1 hand area decreased in SCI patients. In 0–6 m, AIS A grade, or non-cervical injury SCI patients, the degree of M1 hand area MEP hemispheric conversion was positively correlated with total motor score, lower extremity motor score (LEMS), and ADL ability. Multiple linear regression analysis further confirmed the contribution of MEP hemispheric conversion degree in ADL changes as an independent factor.ConclusionThe closer the degree of M1 hand area MEP hemispheric conversion is to that of healthy controls, the better the extremity motor function/ADL ability patients achieve. Based on the law of this phenomenon, targeted intervention to regulate the excitability of bilateral M1 hand areas might be a novel strategy for SCI overall functional recovery.